2018
DOI: 10.1111/anae.14300
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hardness and resilience of i‐gelTM cuffs with temperature: a benchtop study

Abstract: The i-gel is a supraglottic airway with a gel-like thermoplastic cuff. It has been suggested that the seal around the larynx improves following insertion. Perhaps the most intuitive hypothesis proposed for this is that cuff softening occurs during warming from ambient to body temperature. We investigated this using a food industry texture analyser over a wide temperature range. Size 2 and 3 i-gels were secured to a platform within a temperature-controlled water bath, which was in turn mounted on a texture anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…A significant increase in volume (P < 0.001) and weight (3: P = 0.018; 4: P = 0.027; 5: P = 0.006) and a decrease in density (P < 0.001) were observed. A possible explanation for this, besides expansion, is the absorption of fluids, which was also discussed before [5]. The wet milieu, caused by the saliva, could be responsible for this.…”
Section: Discussionmentioning
confidence: 78%
“…A significant increase in volume (P < 0.001) and weight (3: P = 0.018; 4: P = 0.027; 5: P = 0.006) and a decrease in density (P < 0.001) were observed. A possible explanation for this, besides expansion, is the absorption of fluids, which was also discussed before [5]. The wet milieu, caused by the saliva, could be responsible for this.…”
Section: Discussionmentioning
confidence: 78%
“…The improvement in the sealing pressure of the i-gel cuff over time as shown in many studies may be due to the redistribution of the interstitial fluid in the areas around the cuff or due to the interaction between saliva and the cuff material altering its property and allowing it to migrate to a position of better fit. [910]…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Prewarming i-gel laryngeal mask to 42°C would enable the cuff to fit the pharyngeal structure more quickly than if it was stored at room temperature. 5 But Dingley et al 14 evaluated the properties of i-gel cuff over clinical temperature ranges and found that there was a minimal decrease in hardness and resilience with warming.…”
Section: Main Findingsmentioning
confidence: 99%
“…But the melting point of i-gel cuff is above 200°C, whether it will soften as it reaches body temperature after insertion remains controversial in clinical practice. 14 So, the efficiency of prewarming i-gel laryngeal mask for mechanical ventilation remains unclear. [15][16][17] This study aims to investigate the efficiency of prewarming i-gel laryngeal mask for mechanical ventilation by meta-analysis and trial sequential analysis (TSA).…”
Section: Introductionmentioning
confidence: 99%